Electronic nose for robots: electronic nose for alcohol detection - Ibrahim, A. M.; Akmeliawati, Rini; Aslam, Mohd. (LAP LAMBERT Academic Publishing, 2011)
Electronic nose systems are developing in efficiencyand accuracy with the use of variety gas sensors andalso different types of pattern recognition method.This work presents the study of using an artificialolfactory system as a nondestructive instrument todetect and measure concentration of alcohol. Besidesthat, this work also describe how our electronicnose device can be used to detect alcohol in thedrinks, food and so on while at the same time displaythe concentration of alcohol. The hand held unitconsists of an alcohol sensor (TGS 2620), a microcontroller to calculate the concentration of alcoholand control the output and display using LCD.Moreover, the tasks performed at processing data areoutlined and how the concentration of alcohol will becalculated and displayed is presented. The device wastested using a varied range of prepared alcoholmixtures and satisfactory results were observedthrough oscilloscope. The whole system workedfunctional very well; it was able to detect theethanol concentration, it gives various responsevoltages for different set of parameters and it alsoable to give stable response voltage at the presentof ethanol.